Cybercrime investigations the comprehensive resource for everyone - Bandler, John.; Merzon, Antonia (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
Cybercrime continues to skyrocket but we are not combatting it effectively yet. We need more cybercrime investigators from all backgrounds and working in every sector to conduct effective investigations. This book is a comprehensive resource for everyone who encounters and investigates cybercrime, no matter their title, including those working on behalf of law enforcement, private organizations, regulatory agencies, or individual victims. It provides helpful background material about cybercrime's technological and legal underpinnings, plus in-depth detail about the legal and practical aspects of conducting cybercrime investigations. Key features of this book include: Understanding cybercrime, computers, forensics, and cybersecurity Law for the cybercrime investigator, including cybercrime offenses; cyber evidence-gathering; criminal, private and regulatory law, and nation-state implications Cybercrime investigation from three key perspectives: law enforcement, private sector, and regulatory Financial investigation Identification (attribution) of cyber-conduct Apprehension Litigation in the criminal and civil arenas. This far-reaching book is an essential reference for prosecutors and law enforcement officers, agents and analysts; as well as for private sector lawyers, consultants, information security professionals, digital forensic examiners, and more. It also functions as an excellent course book for educators and trainers. We need more investigators who know how to fight cybercrime, and this book was written to achieve that goal. Authored by two former cybercrime prosecutors with a diverse array of expertise in criminal justice and the private sector, this book is informative, practical, and readable, with innovative methods and fascinating anecdotes throughout.
OCLC-licensed vendor bibliographic record.
Keywords: Computer crimes -- Investigation; COMPUTERS / Information Technology; COMPUTERS / Security / General; LAW / Forensic Science